An Investigation into Teachers’ Attitudes to Religious Education in North Macedonia Primary Schools - Adili, Bujar; Ameti, Makfirete; Zenki-Dalipi, Arbresha (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
Religious Education (RE) in North Macedonia holds a significant place in the country's diverse educational landscape, reflecting the coexistence of various faiths within this Balkan nation. This paper aims to investigate teachers’ attitudes toward the impact of Religious Education on students’ behavior, knowledge, and attitudes, considering factors like gender and school type. The study involved 217 primary school teachers from multiethnic regions in North Macedonia. The Teachers' Attitude Questionnaire (TAQ) was employed for data collection. The findings provide insights into teachers' perspectives on the effects of RE. Overall, teachers express positive attitudes towards RE, with a notable percentage acknowledging its positive influence on students’ attitudes towards various aspects of diversity. However, there is variability in opinions regarding its impact on students’ sense of responsibility and behavior. Teachers also diverge in their views on its role in moral development and tolerance promotion. Regarding demographic factors, there is no statistically significant difference in teachers’ attitudes based on gender. However, teachers in multicultural schools exhibit notably more positive attitudes compared to their counterparts in monocultural schools, suggesting that school environment and diversity play a role in shaping perceptions of Religious Education.